3D Crustal Velocity Model for Ground Motion Simulations in North-East India. Issue 3 (23rd February 2021) - Sangeetha, S.; Dhanya, J.; Raghukanth, S. T. G.
ABSTRACT: The present study focuses on developing a 3D crustal velocity model and applying it to perform ground motion simulations for North East India. The study region encompasses area between 89°E to 97°E longitude and 22°N to 30°N latitude. The calibration of the material property is based on 48 shear wave profiles available for the region along with the geotectonic features reported in the literature. The 3D material model arrived from the study is implemented in a finite element framework for ground motion simulations. The developed model is validated using the strong motion data available for four events; 1988 Mw 7.2 India–Bangladesh earthquake, 2011 Mw 6.3 India–Myanmar earthquake, 2013 Mw 5.5 Assam earthquake and Mw 5.2 Bhutan earthquake. The simulations are able to capture the prominent features of the recorded data up to 2Hz. Hence, the developed model can be implemented for estimating ground motions (< 2Hz) in the north eastern region of India. The simulated results can be used to estimate region-specific hazard and the displacement-based design of structures.